1986
DOI: 10.1177/153944928600600205
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Theory: Values Held by Undergraduate Students

Abstract: Thisstudy examined the priorities for theory application and for theory development of 149 students from four different undergraduate occupational therapy curricula. Data were analyzed using Kruskal-Wallis one-way analysis ofvariance by ranks and again using the F test followed by Duncan's Multiple Range Test. Results ofthe two analyses were consistent: Compared to registered occupational therapists, undergraduate students bold higher prioritiesfor theory application and lower priorities for theory development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
(12 reference statements)
0
12
0
Order By: Relevance
“…Finally, the hypothesis expressed above was further tested by adding a sample of undergraduate students in occupational therapy to the survey (Van Deusen, 1986). It was expected that a consistent linear trend would be observed among the three groups (undergraduates, new graduates, and experienced therapists) in terrns of theory valuation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the hypothesis expressed above was further tested by adding a sample of undergraduate students in occupational therapy to the survey (Van Deusen, 1986). It was expected that a consistent linear trend would be observed among the three groups (undergraduates, new graduates, and experienced therapists) in terrns of theory valuation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors in recent years have examined the extent to which occupational therapists value theory (Van Deusen Fox, 1981;Van Deusen, 1985, 1986. In a series of papers published during the past seven years, Van Deusen (1981, 1986 has studied therapists at a variety of points in their careers, with respect to a number of parameters of theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Her findings are consistent with those of Fleming and Piedmont (1989) and those of the present study in that therapists in all surveys were concerned about the lack of recognition of the value of occupational therapy services by third-party payers. Van Deusen's (1985, 1986 studies showed that theory development is related to level of education and length of professional experience. Davidson (1981) suggested that theory valuing had a developmental sequence, beginning with valuing theory application, then research and finally theory building.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings and recommendations fall into different areas relevant to this discussion. These are value of theory developments (Van Deusen, 1981;Barris and Kielhofner, 1985;), clinical reasoning skills (Strong et al, 1995), factors contributing to leadership (Scott, 1985;Burke and DePoy, 1991;Schemm and Bross, 1995), factors influencing the development of master clinicians (DePoy, 1990), knowledge of theories (Javetz and Katz, 1989;Munoz et al, 1993), factors leading therapists to cease practice (Rugg, 1996) or to become administrators or clinicians (Bailey, 1988), whether attitudes towards theory developments are related to educational level (Van Deusen, 1985, 1986, perceptions about occupational therapy education (Fleming and Piedmont, 1989), the move from diploma to degree level (Gape and Hewin, 1995), involvement in research activities (Taylor and Mitchell, 1990), the role of occupational therapy and the practitioner (Adamson et al, 1994;Schwartz, 1995a, 1995b;Clark et al, 1995;Brotherton, 1995a, 1995b;Engquist et al, 1997;Moll and Cook, 1997;Vogel, 1991), professional productivity Mann, 1980a, 1980b;Gilkeson and Hanten, 1984;Clark et al, 1985;Storm, 1990), efficacy of one method for teaching reasoning skills (Neistadt, 1992;Neistadt and Smith, 1997), speciality choice in occupational therapy (Ezersky et al, 1989), and experiences occupational therapists have in their practice (Finlay, 1997) …”
Section: Introductionmentioning
confidence: 99%